Lower limb (healthy leg) compartment syndrome after the patient was in the lithotomy position during the operation: a case study - S.L. Zheng; X. Zhang; J. Lai; X.S. Gao; X.Y. Wang (IMR Press, 2020)
In this case report, we describe compartment syndrome of the lower extremities that occurred during and after the operation in a patient with a gynecologic tumor who underwent minimally invasive surgery in the lithotomy position to prevent venous thrombosis. Lower limb compartment syndrome has also been reported in a number of other similar cases. The use of sequential compression stockings for deep venous thrombosis prophylaxis in patients in the lithotomy position is inappropriate. We expect to have a complete set of guidelines or expert consensus to guide the prevention of venous thrombosis in minimally invasive surgery for patients with gynecologic tumors.